Analisis Hubungan Quadruple Helix Terhadap Keberhasilan Smart Village Di Kabupaten Bojonegoro - Sutrisno Sutrisno; Moehadi Moehadi; Siti Alfiyana; Resa Putri Amalia (CV. Ulil Albab Corp, 2024)
In each country, rural areas account for a portion of the available land; However, these things are generally still outside the mainstream of innovative development processes. It is important to understand the various factors that influence this because each village has unique needs, challenges and resources. These factors include the availability of ICT infrastructure, the level of community digital literacy, government support, access to capital, and active community participation in the planning and implementation process. The aim of this research is to analyze and determine the role of government in the success of smart villages, analyze and determine the role of universities in the success of smart villages, analyze and determine the role of industry in the success of smart villages, analyze and determine the role of society in the success of smart villages. This research method was carried out through quantitative descriptive analysis, the data in this research is primary data in the form of a questionnaire which was measured using a Likert scale. The research results show that the role of government and the role of industry have a significant positive effect on the success of smart villages, while the role of universities and the role of society do not have a significant effect on the success of smart villages.